The growing role of structural mass spectrometry in the discovery and development of therapeutic antibodies. Issue 11 (8th May 2018) - Tian, Yuwei; Ruotolo, Brandon T.
Abstract : The comprehensive structural characterization of therapeutic antibodies is of critical importance for the successful discovery and development of such biopharmaceuticals, yet poses many challenges to modern measurement science. Here, we review the current state-of-the-art mass spectrometry technologies focusing on the characterization of antibody-based therapeutics. Abstract : The comprehensive structural characterization of therapeutic antibodies is of critical importance for the successful discovery and development of such biopharmaceuticals, yet poses many challenges to modern measurement science. Mass spectrometry has evolved into a rapid and sensitive tool for assessing the structures, stabilities, and dynamics of such proteins. Here, we review the current state-of-the-art mass spectrometry technologies focusing on the characterization of antibody-based therapeutics. We conclude by discussing the future of structural mass spectrometry, and its role in enabling the biopharmaceutical pipeline.